2011
DOI: 10.1371/journal.pone.0019503
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase Controls Stem Cell Aging by Regulating BMI1 and EZH2 through MicroRNAs

Abstract: Epigenetic regulation of gene expression is well known mechanism that regulates cellular senescence of cancer cells. Here we show that inhibition of DNA methyltransferases (DNMTs) with 5-azacytidine (5-AzaC) or with specific small interfering RNA (siRNA) against DNMT1 and 3b induced the cellular senescence of human umbilical cord blood-derived multipotent stem cells (hUCB-MSCs) and increased p16INK4A and p21CIP1/WAF1 expression. DNMT inhibition changed histone marks into the active forms and decreased the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 62 publications
7
122
1
2
Order By: Relevance
“…The possibility that SIPS was caused by overexpression of the gene carried by CNs-pDNA and protein accumulation was excluded due to the fact that expressed fluorescent protein was characterized as non-toxic and biologically inert (Henderson and Remington, 2006). Furthermore, among many mechanisms engaged in senescence induction, also DNA and RNA methylation seems to play an important role (Machwe et al, 2000;Oh et al, 2015;So et al, 2011;Young and Smith, 2001). Besides that, DNA methyltransferase II (DNMT2), enzyme with the enigmatic role in the RNA methylation, was found to have protective role in the NPsinduced stress .…”
Section: Independent Of Oxidative Stress-induced Premature Senescencementioning
confidence: 99%
“…The possibility that SIPS was caused by overexpression of the gene carried by CNs-pDNA and protein accumulation was excluded due to the fact that expressed fluorescent protein was characterized as non-toxic and biologically inert (Henderson and Remington, 2006). Furthermore, among many mechanisms engaged in senescence induction, also DNA and RNA methylation seems to play an important role (Machwe et al, 2000;Oh et al, 2015;So et al, 2011;Young and Smith, 2001). Besides that, DNA methyltransferase II (DNMT2), enzyme with the enigmatic role in the RNA methylation, was found to have protective role in the NPsinduced stress .…”
Section: Independent Of Oxidative Stress-induced Premature Senescencementioning
confidence: 99%
“…36 Notably, EZH2 and DNA methyltransferases (DNMTs) are reported to be interacting with and regulated by each other to repress target genes expression including the CDK inhibitors. 37,38 Therefore, despite EZH2, there is possibility that DNMTs such as DNMT1 may also be affected by LDM. We indeed detected a reduction of DNMT1 protein expression by LDM (data not shown).…”
Section: Ezh2 Mediates Lidamycin-induced Cellular Senescence M-q Sha mentioning
confidence: 99%
“…Recently, we reported that the epigenetic regulators histone deacetylase (HDAC) and DNA methyltransferase (DNMT), as well as miRNAs, are important factors for maintaining stemness and for regulating cellular senescence in hMSCs (Jung et al 2010;Lee et al 2011;So et al 2011). Considering that HDAC and DNMT activities decrease in senescent cells, which corresponds with an increase in the expression of their target genes, we treated hMSCs with the HDAC inhibitors valproic acid (VPA) or sodium butyrate (SB) or with the DNMT inhibitor 5-azacytidine (5-azaC) and then examined the cells for changes in AIMP3/p18 expression.…”
Section: Aimp3/p18 Regulates Senescence Phenotypes In Hmscsmentioning
confidence: 99%